THE DEVELOPMENT OF COMMUNICATION AND COMMUNICATIVE SKILLS IN PRIMARY SCHOOL STUDENTS - Umrzakova G. A. (Modern American Journals, 2025)
The article examines the development of communication and communicative skills in primary school students as a central component of their overall personal, social, and academic growth. Communication is not only a linguistic process but also a social and psychological activity that shapes the ability of young learners to interact effectively with teachers, peers, and the wider community. At the primary level, children acquire fundamental language patterns and interpersonal skills that serve as a foundation for future learning and self-expression. This research emphasizes the pedagogical importance of structured approaches to communication, focusing on classroom dialogue, cooperative learning, and play-based interaction. By analyzing contemporary pedagogical theories and practical strategies, the study highlights the necessity of fostering both verbal and non-verbal communicative competence from the early years of schooling. Attention is also given to the role of teachers in modeling communication, designing interactive tasks, and creating a supportive environment where children can practice dialogue, negotiation, and conflict resolution. The research suggests that communicative development is a dynamic process that requires continuous reinforcement through purposeful teaching methods and social engagement. The findings are relevant for educators, methodologists, and policy makers aiming to improve pedagogical strategies and ensure holistic education for primary school students.
Keywords: Communication, communicative skills, primary school students, pedagogy, language development, interaction, teaching methods.